2008
DOI: 10.1007/s12221-008-0091-4
|View full text |Cite
|
Sign up to set email alerts
|

Thin film deposition by PECVD using HMDSO-O2-Ar gas mixture on knitted wool fabrics in order to improve pilling resistance

Abstract: In this work knitted wool fabrics were coated by a Si:O x :C y :H z thin film with the aim to promote pilling resistance. The wool samples were plasma coated in a radio frequency (RF) glow discharge using hexamethyldisiloxane (HMDSO) as the precursor, in mixture with argon and oxygen gases, for different deposition times and reaction pressures, at constant discharge power. Deposited films were characterized by means of Fourier transform infrared (FTIR) spectroscopy and surface morphology by means of scanning e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…More recently, the ability of plasma polymers to retain chemical functionality has been exploited to fabricate non-fouling surfaces, [11][12][13] graft polymer brushes to surfaces, [14] and attach biomolecules to surfaces in order to improve biocompatibility and cell adhesion. [15] Indeed functionalized plasma polymers have found application in a wide variety of areas, including coatings on fibers, [16] improving interfacial adhesion in composite materials, [17] for cell attachment [18] and screening, [19] nanoparticle attachment, [20] biosensors, [21] and as membranes for fuel cells. [22] One class of plasma polymer which has been extensively used is those containing amine groups.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the ability of plasma polymers to retain chemical functionality has been exploited to fabricate non-fouling surfaces, [11][12][13] graft polymer brushes to surfaces, [14] and attach biomolecules to surfaces in order to improve biocompatibility and cell adhesion. [15] Indeed functionalized plasma polymers have found application in a wide variety of areas, including coatings on fibers, [16] improving interfacial adhesion in composite materials, [17] for cell attachment [18] and screening, [19] nanoparticle attachment, [20] biosensors, [21] and as membranes for fuel cells. [22] One class of plasma polymer which has been extensively used is those containing amine groups.…”
Section: Introductionmentioning
confidence: 99%
“…These surfaces have a number of practical applications in various areas such as cleaning coatings [31], biomédical [10], anti-icing [30,32,33], anti-fouling [34,35] and anticorrosion [32], anti-sticking surfaces [36], anti-contamination of glass surfaces such as windows in buildings and windshields in vehicles [37]. Several studies showed a good correlation between hydrophobicity, especially superhydrophobicity and icephobicity of surfaces [7,30,32,[38][39][40][41][42][43]. Hence, the fabrication of hydrophobic and superhydrophobic surfaces has much promise in anti-icing application.…”
Section: IImentioning
confidence: 99%
“…Silicon containing precursors like tetramethylsilane (TMS), tetraethoxysilane (TEOS), and hexamethyldisiloxane (HMDSO) is used for surface modification in textile industries. Among these, HMDSO precursor is nontoxic and nonexplosive and has a high vapor pressure at room temperature than TEOS [35][36][37][38]. Due to the presence of methyl groups; Si, H, and C atoms; and oxygen bond on the HMDSO, it changes the surface of the fabric into hydrophobic [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%